Determination of the Antioxidant Vitamin Levels in Fresh and Dried Bee Pollens in Bingol's Flora - Alayunt, Naci Omer; Karagozoglu, Yusuf; Parlak, Akif Evren; Turkoglu, Semra (Asian Journal of Chemistry, 2013)
In this study, fresh pollens collected from Bingol, province in Turkey were analyzed in June and the dried pollens stored by being kept in a cool, dark place for 8 months at room temperature were analyzed again in February. It was determined that, during this time, there was the maximum loss in the group Adakli with 68.23 % in terms of vitamin A, in the group Gokdere with 70.60 % in terms of vitamin E, in the group Adakli with 71.01 % in terms of vitamin C. These results obtained about the values of vitamin may vary depending on the geographic location where the pollen grows up, the season in which it is gathered and its drying and storage conditions.
Keywords: Bee pollen; Antioxidant vitamins; Bingol